A Combination of PD Controller and PIAFC for Stabilization of âxâ Configuration Quadcopter - Tamami, Niam; Pitowarno, Endra; Astawa, I Gede Puja (Politeknik Elektronika Negeri Surabaya (PENS), 2014)
This paper presents a stabilization control method for âxâ configuration quadcopter. The control method used the combination of PD (Proportional Derivative) controller and PIAFC (Proportional Integral Active Force Control). PD is used to stabilize quadcopter, and PIAFC is used to reject uncertainty disturbance (e.g. wind) by estimating disturbance torque value of quadcopter. The PD with PIAFC provided better result where PIAFC could minimize uncertain disturbance effect. The simulation has successfully give comparation about controller performance (PD, PD-AFC, PD-PIAFC) by calculate RMS (Root Mean Square) value. PD with AFC gives better result than PD. AFC optimization using PI (PD-PIAFC) give best result if compared with PD or PD-AFC. PD-PIAFC has lowest RMS value of result control signal, 0.0389 for constant disturbance and 0.1008 for fluctuated disturbance.Keywords:âxâ configuration quadcopter, stability, PD, PIAFC.